2022
DOI: 10.3389/fgene.2021.785290
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Visualization of Spatial Transcriptomic Data

Abstract: Human and animal tissues consist of heterogeneous cell types that organize and interact in highly structured manners. Bulk and single-cell sequencing technologies remove cells from their original microenvironments, resulting in a loss of spatial information. Spatial transcriptomics is a recent technological innovation that measures transcriptomic information while preserving spatial information. Spatial transcriptomic data can be generated in several ways. RNA molecules are measured by in situ sequencing, in s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 114 publications
(113 reference statements)
0
42
0
Order By: Relevance
“…In multicellular resolution spatial barcoding, each spot can contain transcripts from multiple cells. The cell compositions and regional enrichment of different cell types and cell stages in the spots can be resolved with computational deconvolution, mapping, enrichment, and data-integration-based methods [83] , [84] . For instance, SPOTlight [85] uses non-negative matrix factorization (NNMF) and SpatialDecon [86] log-normal regression for deconvolution of the transcriptomics data, whereas Cell2Location is based on a Bayesian model [87] and Tangram is a deep learning framework to resolve cell types.…”
Section: Spatial Barcoding Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In multicellular resolution spatial barcoding, each spot can contain transcripts from multiple cells. The cell compositions and regional enrichment of different cell types and cell stages in the spots can be resolved with computational deconvolution, mapping, enrichment, and data-integration-based methods [83] , [84] . For instance, SPOTlight [85] uses non-negative matrix factorization (NNMF) and SpatialDecon [86] log-normal regression for deconvolution of the transcriptomics data, whereas Cell2Location is based on a Bayesian model [87] and Tangram is a deep learning framework to resolve cell types.…”
Section: Spatial Barcoding Methodsmentioning
confidence: 99%
“…We focus on methods specialized for ST data analysis. While a detailed description of all the methods mentioned here is beyond the scope of this review, more detailed descriptions of the ST data analysis methods can be found in the original research articles or the recent reviews [27] , [28] , [29] , [83] , [101] , [102] .
Fig.
…”
Section: Advanced Solutions In the Analysis Of Spatial Transcriptomic...mentioning
confidence: 99%
See 2 more Smart Citations
“…Spatial transcriptomics has been widely adopted as a tool to explore genome-wide spatial RNA expression in various tissues 1 . It paves the way to thoroughly investigate the spatial context of cells and their interactions in an unbiased manner 2 . One of the limitations of spatial transcriptomics data is the fact that spots are not directly interpreted as cells.…”
Section: Mainmentioning
confidence: 99%